Cefazolin loaded chitosan nanoparticles to cure multi drug resistant Gram-negative pathogens. (20th January 2016) - Jamil, Bushra; Habib, Huma; Abbasi, Shahid; Nasir, Habib; Rahman, Abdur; Rehman, Asma; Bokhari, Habib; Imran, Muhammad
Highlights: First report of Cefazolin encapsulation in chitosan based nano-carrier systems. Ultra-microscopic study revealed <100 nm size with homogenous dispersion. Concentration dependant encapsulation efficiency varied from 28 to 62%. Highly positive zeta potential +50 mV indicated stable colloidal system. MDR Gram-negative pathogens were effectively inhibited by nano-antibiotics. Abstract: Antibiotic resistance against Gram-negative microbes is considered as an alarming phenomenon that needs to be addressed urgently to develop better therapeutic solutions. The aim of the present research work was to investigate and develop cefazolin loaded chitosan nanoparticles (CSNPs) as a potential tool against multidrug resistant pathogens. Empty and drug loaded CSNPs were prepared by ionic gelation method. It was observed by Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) based studies that CSNPs were less than 100 nm in size and displayed homogeneity both in shape and size. Encapsulation of cefazolin has not increased the size of nano systems. Zeta sizer results revealed that both systems have positive zeta potential of more or less +50 mV, thus contributing towards a stable formulation. Encapsulation efficiency was directly proportional to the increase in the concentration of antibiotic (28–62%). Furthermore, growth kinetics study had demonstrated excellent antimicrobial potential of cefazolin loaded CSNPs against multi drug resistant Klebsiella pneumoniae, Pseudomonas aeroginosa and Extended Spectrum Beta Lactamase (ESBL) positive Escherichia coli.